A review on the best way to produce biodiesel from oil palm wastes / Naseem Fariha Badarudin - Badarudin, Naseem Fariha (Faculty of Plantation and Agrotechnology, 2016)
Oil palm parts and palm oil waste have been used as a source of biofuel like biodiesel Rapid growth of oil palm industry and the method to utilize the parts and waste of oil palm have become a problem to the large amount of waste has been produced by mill daily and only certain types of waste have been reused. Biodiesel that has been produced from the waste has similar properties as fossil fuel that can be directly used as a fuel There are many technologies that are available for processing biodiesel from oil palm. This review gives an overview about the best process that available for processing the oil palm wastes into biodiesel and the sources from oil palm wastes that available for biodiesel production. Different process gives different production cost and different result in biofuel yield. Biofuel can give many advantages to the environment and Malaysia economy. Malaysians should be aware of the benefit of using biofuel and government should commercialize and introduce more about biofuel to automobile industry. With all the information gathered during this review, the best method for producing high yield biodiesel and the best part of oil palm waste that can produce high yield are identified.